Science Teachers Abilities in Integrating Population and Environmental Education with Science Subjects of Junior High School in Mamasa Regency, Indonesia - Mithen, M.; Onesimus, O.; Arfandi, A.; Raeny, R.; Rahmansah, R. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2021)
This study aims to find the ability of science teachers in integrating Population and Environmental Education (Pendidikan Kependudukan dan Lingkungan Hidup/PKLH) with science subjects based on the 2013 Revised Curriculum (K13 Revision) in State Junior High Schools in Mamasa Regency. The study population was 106 junior high schools in Mamasa district with an average of one science teacher per school. Sampling was done randomly, 20% of the population (21 teachers). This study used a single variable, namely the ability of science teachers to integrate PKLH material with science learning in junior high schools. Furthermore, it is translated into five sub-variables, including 1) readiness for teaching, 2) knowledge of K13 Revision, 3) ability to identify PKLH material in junior high school science subjects based on K13 Revision, 4) knowledge of PKLH material, and 5) ability to plan, carry out, and evaluate PKLH learning integrated with junior high school science subjects. The research data results from structured interviews with respondents, and the data analysis technique was carried out in a descriptive qualitative way. The results showed that junior high school science teachers in Mamasa Regency in terms of readiness for teaching, understanding of the K13 Revision, and knowledge of PKLH materials were good. However, the ability to integrate PKLH with science subjects was not good or weak in terms of 1) the ability to identify PKLH material in junior high school science subjects based on K13 Revision, and 2) the ability to plan, carry out, and evaluate PKLH learning integrated with science subjects of Junior High School.